ENHANCING EFL ADOLESCENT LEARNERS’ VOCABULARY ACQUISITION VIA ONLINE SINGLE PLAYER ROLE-PLAY GAMES - Chien-Yu Lin; Yi-Huey Guo (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2021)
With the booming of digital gaming industry, numerous researchers have placed the focus on the use of online role-play games in language learning. However, the research focus of most prior studies was on the commercially-driven “massive multiplayer online role-play games” in the afterschool settings. The use of online single-player role-play games in the class was less studied. The present study hereby investigated sixty-five eighth graders’ use of one online single-player RPG called OzHigh in vocabulary learning. The participants came from three classes in one public junior high school in central Taiwan. By means of a single group design, the participants underwent the game treatment, pre-test, post-test, delayed post-test, questionnaire, and the semi-structured interview. The results showed that the participants had significant improvement on their vocabulary performance. They also responded positively to their role-play game learning experience. Nevertheless, that did not mean that they held negative attitudes toward the traditional face-to-face method of vocabulary instruction. Instead, they confirmed the positive effects of both instructional methods and were aware of the varied learning purposes of these two methods. It is hoped that the findings of this study shed light on language teachers in their efforts to enhance their students’ vocabulary learning.